2021
DOI: 10.1103/physreva.104.063710
|View full text |Cite
|
Sign up to set email alerts
|

One-sided destructive quantum interference from an exceptional-point-based metasurface

Abstract: We propose the concept of one-sided quantum interference based on non-Hermitian metasurfaces. By designing bianisotropic metasurfaces with a non-Hermitian exceptional point, we show that quantum interference can exist only on only one side but not another. This is the quantum inheritance of unidirectional zero reflection in classical optics. The one-side interference can be further manipulated with tailor-made metasurface. With two photons simultaneously entering the metasurface from different sides, the proba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The physical dimensions of the unit cells, such as the size of the gaps, are changed, the effective permittivity is significantly modified, demonstrating that one can achieve MMs with significant tunability by changing the geometry of their unit cells. [ 22 ] Our resonator geometrical pattern distribution and formation have been showcased by Liang et al, [ 49 ] as illustrated in Figure 1b, they demonstrated the quantum interference effect of a two‐port device using an input–output map in the Fock state. Each square cell has been indicated by its output state (row) and input state (column).…”
Section: Modelingmentioning
confidence: 65%
“…The physical dimensions of the unit cells, such as the size of the gaps, are changed, the effective permittivity is significantly modified, demonstrating that one can achieve MMs with significant tunability by changing the geometry of their unit cells. [ 22 ] Our resonator geometrical pattern distribution and formation have been showcased by Liang et al, [ 49 ] as illustrated in Figure 1b, they demonstrated the quantum interference effect of a two‐port device using an input–output map in the Fock state. Each square cell has been indicated by its output state (row) and input state (column).…”
Section: Modelingmentioning
confidence: 65%
“…Meanwhile, EPs have applications in state engineering as well. For example, an EP-induced UZR can provide novel two-photon interference to control two-photon states [19,20]. EP also enables optimal ways to engineer quantum states in a two level systems [50].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the quantum interference in a PT-symmetric waveguide has been shown to be different from that in Hermitian systems [18]. The use of UZR metasurface for photon state transformations [19,20] has also been explored. Chiral quantum state conversions have been experimentally observed in a cold atom system [21].…”
Section: Introductionmentioning
confidence: 99%
“…The metal Cr in this structure causes photon energy loss. Liang et al 166 showed that involving a non-Hermitian exceptional point can modify and manipulate two-photon quantum interference. They used scattering theory to predict and simulate an asymmetric quantum interference device.…”
Section: ■ Nonclassical Metasurfacementioning
confidence: 99%
“…In quantum optics, optical loss and hence the nonhermiticity are detrimental, and therefore researchers have been working hard trying to avoid it. However, very recent studies have shown that non-Hermitian optical systems could be exploited for exotic manipulation of quantum optical states, such as one-sided quantum interference 166 and the insensitivity of the quantum state of light to thermally induce noise in certain non-Hermitian optical systems. 178 These studies open up new possibilities for non-Hermitian optical metasurfaces for potential applications in quantum state preparation and information processing.…”
Section: ■ Concluding Remarksmentioning
confidence: 99%